PENGARUH PENERAPAN MODEL PEMBELAJARAN DISCOVERY LEARNING DENGAN STRATEGI SCAFFOLDING TERHADAP HASIL BELAJAR MATEMATIKA PESERTA DIDIK KELAS VIII SMPN 2 PANGKALAN KURAS - Yonanda, Almirachma (Departemen Matematika, 2025)
The main indicator of how much has been learned is the quality of learning outcomes. However, in fact, learning outcomes in the mathematical field of class VIII at SMPN 2 Pangkalan Kuras are still below the KKTP. The application of discovery learning (DL) model with scaffolding strategy can overcome this problem. This study will explore whether class VIII at SMPN 2 Pangkalan Kuras learn mathematics better using direct learning model or DL model with scaffolding strategy. Quantitative in nature, this study used a posttest-only nonequivalent control group design which is typical of quasi-experimental studies. Class VIII of SMPN 2 Pangkalan Kuras (specifically classes VIII.2 and VIII.3) became the population in this study. A learning outcome test consisting of five questions was used as the instrument in this study. The t-test analysis of the test data resulted in a P-value = 0.044. H0 was rejected as a result of P-value < α. Thus, it can be obtained that in class VIII of SMPN 2 Pangkalan Kuras, the DL model with scaffolding tactics produces learning outcomes that are superior to direct learning.Keywords– Mathematics Learning Outcomes, Discovery Learning Model, Scaffolding Strategy, Direct learning Model